Pengaruh Kualitas Pelayanan, Kepercayaan, dan Customer Value terhadap Loyalitas Konsumen pada Artha Lintas Data Mandiri Kediri - Nisak, Vira Izzatun (Jurnal Cendekia Manajemen (JCM); Vol 2 No 1 (2024): MarchDO - 10.32503/jcm.v2i1.5805, 2024)
This study discusses the Effect of Service Quality, Trust, and Customer Value on Consumer Loyalty at Artha Lintas Data Mandiri Kediri. The method used in this study is quantitative. The sample used in this study is the number of consumers who subscribe from July 2023 to December, 2023 totaling 112 samples. The sampling technique used in this study used Purposive Sampling. Data analysis in this study uses Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression, Coefficient of Determination (RÂ²), t Test and f Test. The result of this study is that Service Quality has a partial effect on Consumer Loyalty with a significant value of 0.002<0.05. Trust has a partial effect on Consumer Loyalty with a significant value of 0.000<0.05. Customer Value has a partial effect on Consumer Loyalty with a significant value of 0.024<0.05. Service Quality, Trust and Customer Value simultaneously affect Consumer Loyalty with a significant value of 0.000< 0.05.